МИРТЕМИР - ҚОРАҚАЛПОҚ АДАБИЁТИНИНГ МОҲИР ТАРЖИМОНИ - Қурамбоева, Г. (SCIENCE and SOCIETY, 2019)
The article considers the connection of Mirtemir with Karakalpak literature, translation of Berdakh’s poems, as well as the epos “Kirk kiz” into Uzbek.